Consumer Protection in Binding Sale and Purchase Agreements of Subsidized Housing - Muhammad Zufar Aminullah (Journal of Law and Social Politics, 2026)
Subsidized housing is an important instrument in providing affordable housing for low-income people. However, the practice of Binding Sale and Purchase Agreement (PPJB), which is generally made unilaterally by developers, often raises legal problems. Many PPJBs contain standard clauses that are detrimental to consumers, such as delays in submission or non-conformity with specifications, thereby weakening the consumer's position in the contractual relationship. This study emphasizes the importance of legal protection for consumers of subsidized housing by reviewing the provisions in Law Number 8 of 1999 concerning Consumer Protection, Law Number 1 of 2011 concerning Housing and Residential Areas, and Minister of Public Works and Public Housing Regulation Number 11 of 2019 concerning PPJB. Article 18 of the UUPK expressly prohibits the inclusion of clauses that are detrimental to consumers and declares them null and void. Therefore, strengthening regulations, law enforcement, and public awareness is crucial to create fair and balanced consumer protection in subsidized housing transactions.